Pengaruh Brand Personality dan Kualitas Produk Terhadap Keputusan Pembelian pada Produk Laptop HP (Studi Pada Mahasiswa di Kota Malang) - Erick Eka Prasetya; Yekie Senja Oktora; Ayu Sulasari (INDO PUBLISHING, 2026)
The increasingly intense global laptop industry competition drives every brand to rely not only on technical specifications, but also on building brand personality and product quality that can influence consumer purchase decisions. HP, as one of the world's largest laptop brands, still faces competitive market dynamics. Inconsistencies in previous research findings, serve as the basis for this study. This study aimed to determine and analyze the effect of brand personality and product quality on HP laptop purchase decisions among students in Malang City, both partially and simultaneously. This study employed a quantitative approach with a survey method. The sample consisted of 100 respondents determined using the Cochran formula and purposive sampling technique. The respondents were active students from three state universities in Malang City who had purchased and used HP laptops as their primary device to support academic activities. Data were collected through a Likert scale questionnaire and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, the coefficient of determination, t-tests, and F-tests with the assistance of IBM SPSS Statistics 25. The results indicated that brand personality had a positive and significant partial effect on purchase decisions. Meanwhile, product quality also had a positive and significant partial effect on purchase decisions. Simultaneously, brand personality and product quality together had a significant effect on purchase decisions. Product quality was found to be the most dominant variable compared to brand personality. This indicates that purchase decisions for HP laptops can be shaped through the strengthening of positive brand personality and product quality that meets student expectations.